Incidence of the methodology applied in teaching a foreign language to students from Advanced Intensive English I, of the Bachelor of Arts in English with emphasis in teaching, semester II-2015, in the Department of Foreign languages of the University of El Salvador in San Salvador, in comparison with the students from Advanced Intensive English I, of the Bachelor of Arts in English with Emphasis in Teaching, semester II-2015, in the Department of Foreign Languages of the University of El Salvador in Santa Ana - Vásquez Rodríguez, Karen Elizabeth
In this project, the aim was to determine the incidence of the methodology used to teach English in the subject of Advanced Intensive English I to students of the Bachelor of Arts in English with emphasis in Teaching in both campuses, in the Department of Foreign Languages in San Salvador, in comparison with, the Department of Foreign Languages in Santa Ana . For that reason, the researchers investigated about the methodology through the activities and techniques that instructors apply to teach English. As part of the data needed, the syllabus of the subject from each campus was obtained in order to get further information related to the methodologies to make a comparison chart. Activities and techniques were sorted out in order to know what method used in the past they come from. For that reason, the researchers presented a little review of the most important methods used in the past to teach a foreign language. From the mid-1880s to the mid-1980s century, the language teaching profession was involved in a search for what was popularly called “methods”, that would successfully teach students a foreign language in the classroom. Historical accounts of the profession tend therefore, to describe a succession of methods. Edward Anthony (1963) gave us a definition of method, and it is described as an overall plan for systematic presentation of language based upon a selected approach. Another concept of method was given by Richards and Rodgers(1986). They say that methods are the essential building blocks of methodology which are realized by various techniques. By the nineteenth century, the systematic study of the grammar and of the classical texts re-emerged in schools and universities. It marked the appearance of the Grammar Translation Method. This method requires the students to learn the rules of grammar and bilingual lists of vocabulary. Grammar was learned deductively by means of long and elaborated explanations. All rules were learned with their exceptions and irregularities explained in grammatical terms By the end of the nineteenth century, the Direct Method demanded the ability to use rather than to analyze a language, and it became a viable alternative to the Grammar Translation Method. The time passed and in the first half of the twentieth century, the Direct Method did not take too much relevance in the United States as it did it in Europe. While one could easily find native-speaking teachers of modern foreign languages in Europe, such was not the case of the United States. The Audio-lingual Method was also known as the Aural-oral, functional skills; or American Method of language teaching, was considered a “scientific” approach to language teaching. Chastain (1976) affirms that students learn languages through stimulus-response techniques. Students should learn to speak without attention to how the language is put together. Meanwhile, in North America, the Ccommunicative Language teaching was the product of educators and linguists who had grown dissatisfied with the Audio-lingual Method; because they felt that students were not learning enough realistic language; in other words, students were at loss to communicate in the use of the language studied. Different ways of language teaching lead to different techniques applied in the classroom, according to the purpose of the goals for teaching the language those techniques are divided in three categories; controlled technique, semi-controlled technique and free technique. With the information mentioned above, the aim of this research was to know about the effectiveness of the techniques that instructors applied in their methodologies.